ECONOMIC EFFICACY OF DIFFERENT FUNGICIDES FOR THE CONTROL OF LEAF SPOT OF CAULIFLOWER - ABU MOHAMMAD, B. P. SINGH, S. P. SINGH AND (Indian Phytopathology, 2002)
Leaf spot caused by Alternaria brassicae inflicts severe damage to cauliflower right. from germination till harvest and also in storage and transit. The pathogen produces various types of symptoms like damping-off, seedling blight, stump rot, leaf spot, leaf blight and curd rot. Seven fungicides, namely, ernisan-S, bavistin, captaf, cuman-L, difolatan, dithane M-45 and dithane Z-78 were tested under field conditions for suggesting economically viable control measures acceptable to farmers. Three sprays with difolatan (0.2 per cent) distinctly scored over other fungicides, both in terms of additional crop yield (137.03 q/ha) and net profit (Rs. 9554.47/ha) with a benefit-cost ratio of 13 : 2.